Environmental sustainability concerns - International Symposium on Environmental Sustainability (2006 : Environmental Engineering Division, BUET); Mujibur Rahman, Md.; Bangladesh University of Engineering and Technology. Environmental Engineering Division; Centre for Environmental and Resource Management (Dhaka, Bangladesh); ITN-Bangladesh (Network) (Dhaka : Environmental Engineering Division : Centre for Environmental and Resource Management : International Training Network Centre, BUET, 2006)
Papers presented at the international symposium organised by Environmental Engineering Division and others, during 7-9 Feb. 2006, BUET, Dhaka.
Includes statistical tables.
Includes bibliographical references.
Keywords: Environmental protection -- Bangladesh -- Congresses; Sustainable development -- Bangladesh -- Congresses